Researching L2 Motivation and Identity in the Indonesian Islamic School Context: an Insight into Research Opportunities - Achmad Farid; Adi Yusuf (Journal of Research in Foreign Language Teaching (JRFLT), 2022)
Motivation is one of the most important factors affecting foreign language learning. Some studies suggest that motivation has a robust impact on foreign language learning outcomes regardless of learners’ language talent (Wigfield & Wentzel, 2007; Rehman & Haider, 2013; Islam et al., 2013). This is why motivation becomes the most ‘complex and challenging’ problem faced by teachers (Scheidecker and Freeman, 1999). Motivation can shape learners’ attitude, objective (Maehr & Meyer, 1997), increase learners’ learning effort (Pintrich, et al., 1993), and improve learners’ achievement. However, motivation becomes a more intricate issue in the context of pesantren school in Indonesia (Farid and Lamb, 2020). That is because pesantren consists of learners from various socio-economic backgrounds. While pesantren students’ main aim is to learn religious knowledge, some of them perceive learning English irrelevant to their future. Based on contemporary theories on L2 motivation and identity and utilising the authors’ years of experience as they work as English instructors in the pesantren environment, this paper attempts to shed light on possible topics that can be explored by future L2 motivation researchers in Indonesia, especially in the pesantren context.